Mifepristone Increases Life Span in Female Drosophila Without Detectable Antibacterial Activity - Landis, Gary N.; Riggan, Luke; Bell, Hans S.; Vu, William; Wang, Tianyi; Wang, Ina; Tejawinata, Felicia I.; Ko, Sebastian; Tower, John (Frontiers in Aging, 2022)
Mifepristone dramatically increases the life span of mated female Drosophila while reducing the expression of innate immune response genes. Previous results indicated that mifepristone also reduced the load of aero-tolerant bacteria in mated females. Experiments were conducted to further investigate the possible role of bacteria in mifepristone life span effects. Life span was assayed for flies grown from sterilized eggs on autoclaved media, and for normally-cultured controls, in two independent assays. Sterilization increased mated female life span (+8.3% and +57%, respectively), and the effect of mifepristone was additive (+53% and +93%, respectively). High-throughput sequencing of 16S sequences revealed that sterilization reduced the abundance of multiple species, and the classes Bacteroidia, Bacilli, Actinobacteria and Cytophagia. By contrast, mifepristone caused no decreases, and instead increased the abundance of three species. Five aero-tolerant bacterial species were cultured from extracts of mated female flies, including both gram-positive and gram-negative species (Acetobacter sicerae, Enterococcus faecalis, Lactobacillus plantarum, Serratia rubidea, and Paenibacillus glucanolyticus). There was no detectable effect of mifepristone on growth of these bacteria in vitro, indicating that mifepristone does not have a direct antibiotic effect. To test if antibiotics could mimic the effects of mifepristone in vivo, mated female flies were treated throughout adult life span with high concentrations of the individual antibiotics doxycycline, ampicillin, kanamycin and streptomycin, in replicate experiments. No significant effect on life span was observed for ampicillin, kanamycin or streptomycin, and an inconsistent benefit was observed for doxycycline. Finally, supplementation of media with Enterococcus faecalis did not alter adult female life span in the presence or absence of mifepristone. Taken together, the results indicate the life span benefits of mifepristone are not due to an antibiotic effect.